Fibrotomy: Breaking the Chains of OSMF - Ankita Sahare (UNIVERSITY JOURNAL OF DENTAL SCIENCES, 2026)
Oral Submucous Fibrosis (OSMF) is a chronic, insidious, and potentially malignant disorder of the oral cavity characterized by inflammation and progressive fibrosis of the submucosa. It predominantly affects populations in the Indian subcontinent and Southeast Asia, with areca nut and betel quid chewing identified as the primary etiological factors. The condition results in mucosal stiffness, trismus, burning sensation, dysphagia, and carries a significant risk of malignant transformation. Various management strategies, including conservative, medical, and surgical interventions, have been explored .